A D-peptide-based HIV gelatinous combination vaccine improves therapy in ART-delayed macaques of chronic infection. (February 2022) - Liu, Ye; Ji, Xiaolin; Liu, Ying; Li, Dan; Cun, Yupeng; Zhang, Ye; Wang, Ruixin; Hao, Yanling; Wang, Shuo; Chen, Chunying; Shao, Yiming
Highlights: Using a one-step method to construct a new D-peptide-based gelatinous combination vaccine (GCV). First to realize the efficient co-delivery of multiple types of HIV antigens and IL-21 adjuvant in non-human primates. Optimizing the quality of immune responses and suppressing viral loads and reservoir in chronically infected rhesus macaques. Identifying a checkpoint gene, MAMU-B, for mediating the immunoregulation of GCV in vivo . Graphical Abstract: The one-step construction of a new D -peptide-based GCV for the persistent suppression of viral loads and viral reservoir in ART-delayed macaques of chronic infection. ga1 Abstract: Improving virus control in HIV-infected individuals without a timely antiretroviral therapy (ART) intervention still remains an important challenge, which is largely due to the lack of a potent means to co-deliver a complex therapeutic system consisting of diverse types of vaccines and drugs to the human body. Here, we used a one-step method to rapidly construct a new D -peptide-based gelatinous combination vaccine (GCV), which possesses a potent loading capacity for diverse types of antigens and a sustainable release profile, and exhibits efficient internalization by dendritic cells (DCs). As a novel immunization strategy, GCV can efficiently co-deliver two critical HIV antigens (Env and Gag) in combination with a potent immunostimulator, interleukin 21 (IL-21), in a controllable and balanced manner to induce a high-quality immune response against HIV chronic infection in non-human primates. In SHIV-SF162P3-challenged rhesus macaques initiating ART at week 8 of infection (a chronic infection model), GCV simultaneously activated the critical polyfunctional CD4 + and CD8 + T cell response which has never been reported in existing vaccination strategies. More importantly, GCV elicited a persistent suppression against viral loads (10–100 fold) and viral rebound, as well as eliminated the viral reservoir following ART discontinuation. These findings describe a new and promising therapeutic vaccine candidate for realizing a functional cure against chronic HIV infection.